A four-foot walking-type stepping piezoelectric actuator: driving principle, simulation and experimental evaluation. (25th September 2018) - Xu, Dongmei; Liu, Yingxiang; Liu, Junkao; Wang, Liang
Abstract: A four-foot walking-type piezoelectric actuator using non-resonant bending transducers, inspired by the movements of quadrupeds, was proposed and tested to achieve driving abilities of both long stroke and high resolution. Two transducers operated under bending hybrid modes were used together to simulate the stepping motion of a quadruped: the rectangular trajectory movements of the driving feet were generated by a combination of designed bending motions and the runners were pushed linearly step-by-step. The simulation analyses were carried out by using a finite element method to verify the driving trajectory. Finally, a prototype was manufactured to further verify the driving mechanism and to evaluate the output characteristics. The step displacement, maximum no-load velocity and maximum thrust of the prototype are 8.23 μ m, 1.65 mm s −1 and 12 N respectively. This work provides a new driving mechanism for the design of non-resonant piezoelectric actuators with simple structure, long stroke, high resolution, high velocity and large output thrust by utilizing the bending motions of two sandwich transducers.